Preservation of the middle meningeal artery during unruptured aneurysm surgery: an independent risk factor for postoperative chronic subdural hematoma - Kim, Myungsoo (Frontiers in Neurology, 2024)
Background: Although microsurgical clipping for unruptured aneurysms has become safer and more efficient with modern neurosurgical advances, postoperative chronic subdural hematoma (CSDH) persists as an underrecognized complication. This study investigated the association between preservation of the anterior branch of the middle meningeal artery (MMA) during surgery and CSDH development.Methods: We retrospectively reviewed 120 patients who underwent clipping for unruptured aneurysms at Kyungpook National University Chilgok Hospital between May 2020 and July 2023.We evaluated the patients on the basis of surgical approach-lateral supraorbital (LSO) or standard pterional craniotomy-and the status of the MMA postoperatively. We employed pre-and postoperative MR angiography to assess MMA preservation and used follow-up computed tomography scans to monitor CSDH development.Results: Of the 120 patients, 22 (18.3%) developed CSDH. Univariate analysis revealed that male sex, advanced age, and MMA preservation are risk factors for postoperative CSDH. Multivariate analysis supported these findings, indicating a significant association with the development of CSDH. MMA preservation was reported in 65 patients, of whom 60 and 5 underwent LSO and pterional craniotomy, respectively.Conclusion: Preservation of the anterior branch of the MMA during unruptured aneurysm surgery is a risk factor for postoperative CSDH development. Advanced age and male sex also contribute to the increased risk. These findings highlight the need for further investigation into surgical techniques that could mitigate postoperative CSDH development.